Effectiveness of psychotherapy in the treatment of social anxiety in Latin American adults - Segovia Vega, Luis Alejandro (2025)
Social anxiety is currently one of the most prevalent mental disorders worldwide. Generating limitations at a personal, family, social and work level. The objective of this research is to know the effectiveness of psychotherapy in the treatment of social anxiety with the adult population in Latin America. Methodology: A review of the scientific literature related to the object of study will be carried out through a search in the databases of the following search engines: Scopus, PubMed and Scielo. Results: The search carried out in the different databases resulted in 87 potentially relevant articles, of which five articles were selected that met the inclusion criteria proposed for this research. Conclusions. The analysis carried out suggests that psychotherapeutic intervention is effective for the treatment of social anxiety disorder. There is a need to carry out further studies in this regard.